2016
DOI: 10.1002/vms3.29
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence ofToxoplasma gondiiDNAin goats’ milk and seroprevalence in Northwest Tunisia

Abstract: Toxoplasmosis is a worldwide zoonosis with high impact on human and animal health. Consumption of unpasteurized milk is a risk factor of human toxoplasmosis. The aim of this study was to estimate the seroprevalence and molecular prevalence of T. gondii in goats’ milk in Northwest of Tunisia (Jendouba Governorate). A total number of 77 blood samples were collected from six herds were screened with a commercial ELISA kit for T. gondii antibodies. For the same goats’ samples, a nested PCR was performed to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 36 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…Many different molecular techniques are used for diagnosis of T. gondii in milk samples as conventional PCR [ 18 , 19 ], nested PCR [ 23 ], PCR-RFLP technique [ 24 ], and qPCR [ 25 , 26 ]. qPCR assay is the most rapid, accurate, and effective molecular technique that can be used for Toxoplasma detection [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many different molecular techniques are used for diagnosis of T. gondii in milk samples as conventional PCR [ 18 , 19 ], nested PCR [ 23 ], PCR-RFLP technique [ 24 ], and qPCR [ 25 , 26 ]. qPCR assay is the most rapid, accurate, and effective molecular technique that can be used for Toxoplasma detection [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with sheep, T. gondii infection was studied in other species such as goats and horses [10,33]. To assess the risk of toxoplasmosis transmission through contaminated food, one study was conducted in goat milk samples, reporting a molecular infection rate of 7.8% [9]. Detecting parasite DNA in milk does not mean that the parasite is alive; further studies are needed to determine parasite viability.…”
Section: Toxoplasma Gondii Infection In Algeriamentioning
confidence: 99%
“…; Amairia et al . ). It has been shown that insemination, using experimentally contaminated fresh semen with different T. gondii tachyzoites concentrations was able to transmit infection to sheep, indicating the possibility of a sexual transmission route (Bezerra et al .…”
Section: Introductionmentioning
confidence: 97%